Interactions between business conditions, economic growth and crude oil prices - Sodeyfi, Setareh; Katircioglu, Salih (Routledge Journals, Taylor & Francis Ltd, 2016)
This study aims to research the empirical relationship between business conditions (BCs) and crude oil prices by employing a time series analysis for a panel of regions. BCs have been proxied by real income and real industrial production (IND) as advised in the relevant literature. Results suggest that economic activity and industrial value added are in a long-term relationship with oil price movements in the selected countries and regions. Gross domestic product (GDP) and IND are significantly affected by oil prices worldwide. Real income converges to long-term paths significantly, but at low levels through the channel of oil price movements. Oil price has a negative impact on business activities in some countries while it has a positive impact in others. Therefore, the sign of coefficient of oil prices on business conditions has found significant in this research study.
Keywords: Business conditions (BCs); oil; error correction model (ECM)